UJI ANTIOKSIDAN EKSTRAK ETANOL BIJI KOPI ARABIKA (Coffea arabica L.) LERENG GUNUNG ARGOPURA KABUPATEN JEMBER PADA BERBAGAI KONDISI PENYANGRAIAN - Pebriarti, Iski Weni; Diana, Agustin Nourma (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Coffee (Coffea arabica L.) is a plant which has been cultivated in Indonesia and it is one of natural source of antioxidants. The main bioactive component which contain antioxidant properties is chlorogenic acid. The roasting process can cause chlorogenic acid in coffee beans to decrease as the temperature increases and the length of roasting, so the way coffee is served as a source of antioxidants which may need to be considered. The purpose of this study was to determine the group of compounds and antioxidant activity contained in Arabica coffee beans obtained from the slopes of Mount Argopura at various conditions of roasting. The samples of Arabica coffee beans each done roasting in advance at a temperature of 160°C - 180°C; 190°C - 210°C; and 220°C - 240°C before it is milled. The used of extraction method is maceration using 80% ethanol solvent. Antioxidant activity testing was done by DPPH method. Antioxidant activity is expressed based on the IC50 value (Inhibitor Concentration 50%). The highest value of antioxidant activity was obtained from Arabica coffee beans roasted at a moderate temperature with a value of IC50 26.41 ± 0.182 ppm. The result of the T-test obtained a sig value < 0.05 which indicates a difference in the antioxidant activity produced by the extract of Arabica coffee beans at various conditions of roasting.